Management Of Maxillary Midline Diastema (MMD) With Removable Orthodontic Appliance - Queneessa Cahya Albetra; Aya Dini Oase Caesar (CV. AFDIFAL MAJU BERKAH, 2026)
Maxillary midline diastema (MMD) is a space between the middle incisors of the upper jaw which is often an aesthetic problem in adolescents and young adults because it can affect the appearance and decrease the patient's confidence. This condition has a multifactorial etiology, such as genetic factors, high labial frenulum attachment, bad habits of the oral cavity, and impaired growth and development of teeth. In mild diastema cases, the use of removable orthodontic devices can be a treatment option because it is simple, conservative, and effective in correcting the position of the teeth. This case report aims to describe the management of the maxillary midline diastema using removable orthodontic devices. A 19-year-old woman came to the Soelastri Dental and Oral Hospital with a complaint of a gap in the anterior teeth of the upper jaw that interfered with appearance and confidence. Patients also complained that food often got stuck between the teeth and complaints had been felt since high school. The results of the examination showed the presence of a maxillary midline diastema between teeth 11 and 21. Treatment is performed using a removable orthodontic device with an active component of the finger spring for the correction of the central diastema. The patient underwent treatment for 6 months accompanied by regular control and activation of the device. The results of the treatment showed a satisfactory closure of the diastemic space. The use of removable orthodontic devices is effective in correcting mild cases of maxillary midline diastema and can improve the patient's aesthetics and confidence.